Pertanggungjawaban Bagian Hubungan Masyarakat Dalam Melakukan Monitoring Dan Evaluasi Dalam Penyelenggaraan Transparansi Publik - Agus Iskandar PP. (Universitas Bandar Lampung (UBL), 2015)
Public Information Service Standards. Providing public information as liability in government. The main problem in implementing this research include: a. How is a form of the Regional Secretariat of Public Relations in monitoring and evaluation of the news media in the administration of public transparency. Approach to the problems that are used in this research conducted by using the normative juridical approach. The data used in this study secondary data obtained from library. The conclusion of this study are liability of Public Relations Regional Secretariat of West Tulang Bawang in monitoring and evaluation of the news media in the administration of public transparency that information to the public Implementation Report activity using the principles of accountability and transparency, but the implementation is not maximized. Suggestions in this study that the Government of West Tulang Bawang obliged to use all of the criteria of public information as set forth in the Act Public Information so as to realize liability and transparency.